Kombinasi Aromaterapi dan Back Massage Terhadap Maternal Depressive Symptoms Postpartum - Lalita, Elisabeth MF; Adam, Yulien; Donsu, Amelia; Kuhu, Fonnie; Manueke, Iyam (POLTEKKES KEMENKES MANADO, 2023)
Background : The postpartum period is a period of increased risk of depression and other mental disorders as a result of physiological and psychosocial changes. Postpartum maternal depression, such as feelings of stress, excessive anxiety, difficulty sleeping, and weight changes with drastic weight loss, if left unchecked can be harmful to both the baby and the mother herself, thus postpartum mothers need to improve screening and treatment. Postpartum depression requires greater treatment depending on the severity. Evidence suggests that more than 50% of people suffering from anxiety and depression use some type of complementary health approach, including herbal remedies, dietary supplements, massage, and aromatherapy. Objective : analyze the effectiveness of treatment aromatherapy and back massage towards maternal depressive symptoms postpartum. Methods : Research design Quasi experimental design with a plan one group pretest posttest. Place of research implementation in the city of Manado. Samples were 4 to 8 weeks postpartum mothers who were taken randomly purposive sampling totaling 32 subjects, analysis by test Wilcoxon Test. Results : research shows a combination of aromatherapy and back massage proven to significantly reduce maternal depressive symptoms postpartum. This treatment helps in promoting relaxation, pain relief, and less sleeplessness during the postpartum period. This result is supported by various literatures and can be recommended for families.